2006
DOI: 10.1002/cncr.22379
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin and gemcitabine with either vinorelbine or paclitaxel in the treatment of carcinomas of unknown primary site

Abstract: Recent advances have documented the development of lung vasculature before and after birth, but less is known of the growth and maturation of airway vasculature. We sought to determine whether airway vasculature changes during the perinatal period and when the typical adult pattern develops. On embryonic day 16.5 mouse tracheas had a primitive vascular plexus unlike the adult airway vasculature, but instead resembling the yolk sac vasculature. Soon after birth (P0), the primitive vascular plexus underwent abru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 87 publications
0
25
0
1
Order By: Relevance
“…There were seven RCTs (Shildt et al , 1983; Dowell et al , 2001; Assersohn et al , 2003; Culine et al , 2003; Palmeri et al , 2006; Huebner et al , 2009; Hainsworth et al , 2010) and one non-randomised trial (Saghatchian et al , 2001) where two treatment arms were evaluated. Six of the included clinical trials primarily explored or estimated the treatment outcome separately; only one phase III trial had a primary objective of directly comparing the two treatment regimens (Hainsworth et al , 2010).…”
Section: Resultsmentioning
confidence: 99%
“…There were seven RCTs (Shildt et al , 1983; Dowell et al , 2001; Assersohn et al , 2003; Culine et al , 2003; Palmeri et al , 2006; Huebner et al , 2009; Hainsworth et al , 2010) and one non-randomised trial (Saghatchian et al , 2001) where two treatment arms were evaluated. Six of the included clinical trials primarily explored or estimated the treatment outcome separately; only one phase III trial had a primary objective of directly comparing the two treatment regimens (Hainsworth et al , 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Phase II studies evaluating these agents combined with a platinum compound, including clinical trials in patients with CUP, were successively performed and reported. [18][19][20][21][22] Many of these studies obtained a response rate of about 30% and an overall survival of less than 10 months. [18,19] In these studies, an overall survival of longer than 10 months was obtained in patients who received combined chemotherapy with a platinum preparation plus taxane.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of regimens containing a platinum and gemcitabine for CUP since year 2000 have reported objective response rates of~50% and median OS of up to 13.6 months, which is comparable to the platinum-taxane combinations. 22,23 European investigators compared the effect of single-agent cisplatin with gemcitabine and cisplatin combination on survival in goodrisk patients with CUP. Although the results of this prospective trial were expected to clarify the role of combination chemotherapy in good-risk patients with CUP, the trial was stopped due to insufficient accrual, and the result showed a non-significant trend towards higher survival with gemcitabine plus cisplatin as compared to that with cisplatin alone.…”
Section: Discussionmentioning
confidence: 99%